The Process Of Performer Presence And Audience Participationdanto Criticism On Marina Abramovic “The Artist Is Present” - Saberian, Farinaz; Hessami, Mansour (The Turkish Online Journal of Design Art and Communication, 2016)
Marina Abramovic is an artist whose work is astonishing same as her life. She uses her body as main subject and media of her art. This Serbian artist living in New York, rose to fame in mid 70s through her creative performance which were created collaborating Oley, German artist. When they finished working together after 23 years, Marina Abramovic kept on her work alone and eventually became the most famous female performance artist who was the person that converted performance to an institutionalized shape of art. Her performances are personal and physically and emotionally are overt and risky. In her performance, this artist put commonplace actions as criteria to be able to reveal their hidden power through this. She believes that an artist should suffer because the best works will be manifested through pain. Pain brings transfiguration with itself and artist’s spirit will excellence. Prominent indexes in her performances include the relationship between artist as performer and audience, physical tolerance and mental concepts facilities. One of the most famous performances of her is called “the artist is alive” which had been proposed in New York modern art museum in 2010 in seven hundred and thirty six hours (during three months). Arthur Colman Danto, American Philosopher and contemporary art critic also participated in mentioned performance, an excellent master or philosopher who is considered as one of the most famous theoretician in field of art. This performance is the longest history performance and the most alive show which is held in this museum up to now. In current article, mentioned work will be analyzed. The question is that what the goal of mentioned artist is about performing this work and what concept is hidden beyond this performance.
Keywords: Marina Abramovic; Arthur Danto; conceptual art; performance art; investigating “the artist is present”